PENGARUH HARGA EMAS DUNIA, HARGA MINYAK DUNIA, DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM SEKTOR PERTAMBANGAN PADA BURSA EFEK INDONESIA PERIODE 2016-2019 - Shella, Hesti May; Damayanti, Damayanti; Harori, M. Iqbal (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the effect of world gold price, crude oil price, and Rupiah exchange rate to mining stock price of Bursa Efek Indonesia 2016-2019 period. This type of research uses explanation with quantitative approach and sampling using saturated sample technique or census obtained by 48 amount of data. The analysis method used in this research is statistic analysis and regression test using SPSS 23 software. The results of this study indicate that partially crude oil price has a significant effect on mining stock price. Meanwhile, partially world gold price and Rupiah exchange rate do not have a significant effect on mining stock price. Then, simultaneously world gold price, crude oil price, and Rupiah exchange rate has an influence on mining stock price.